TINJAUAN LITERATUR SISTEMATIS PENERAPAN DMAIC DAN DMADV DI INDUSTRI MANUFAKTUR - Putri, Fattiya Hamada Sakti Issa; Pradana, Bintang Candra; Kusuma, Dita Ameilya; Adhani, Febryan Zidane; Ramadhan, Galih; Ariyansyah, Ferdhika; Ahmadi, Fatur Rahman; Aziz, Febri Dwi Nur (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2022)
Manufacturing company activities consist of several activities, one of which is management. The Process Management Framework includes activities to develop, improve and manage business processes in manufacturing companies. Some companies use some of the best methodologies to improve or develop existing processes and develop new ones. This literature aims to analyze the application of the Define, Measure, Analyze, Improve, Control (DMAIC) and Define, Measure, Analyze, Design, Validate (DMADV) methods in the Manufacturing Industry. The method used is Systematic Literature Review. These results indicate that the DMAIC and DMADV methods are methods that drive the pace of industrial economic growth, because they reduce process variability and improve product quality and prevent errors from occurring. However, this process requires trained and experienced personnel to meet the demand for product defect reduction. This method is the choice of industries that want to improve product quality and avoid mistakes, even though it takes a long time to implement, but almost all problems can be solved and improve processes in the manufacturing industry.